Strategy of Handling Slum Areas in an Effort to Support the Development of the National Tourism Strategic Area (KSPN) of Lake Toba in the Pangururan Cluster of Samosir Regency - Yondra, Ary; Andayani, Lita Sri; Rujiman, Rujiman (Budapest International Research and Critics University, 2021)
This research has the background of Slum Decree No. 110 of 2020 Samosir Regency, Lake Toba National Tourism Strategic Area, inadequate residential environmental facilities and infrastructure. The purpose of this study is to analyze the level of slum slums and Pardomuan Village 1, analyze space patterns in slum deliniation areas to residential areas, analyze community participation in the handling of slum areas, and analyze strategies for handling slum areas in an effort to improve the quality of settlements. The methods used in this study are qualitative and quantitative approaches, and mixing. The total population of 2,490 family heads and a sample of 95 family heads. The data source is obtained from primary data, which is data obtained directly from respondents. And secondary data is obtained from village-level planning documents and policy documents at the District level. The results of this study are (1) The level of squalor of The Village of Pangururan Village Market and Pardomuan Village 1 has a mild slum status; (2) The results of overlaying the river border area and the distribution of settlements at the research site obtained a total of 75 units of buildings in line with the river border area; (3) The role of the community to maintain the environmental infrastructure of settlements, the role of community leaders, institutional influences and relationships and beliefs between individuals, is part that must be considered in strategizing the handling of slum areas in research locations; and (4) The results of SWOT analysis with S-O strategy that uses Strength to utilize Opportunity, obtained strategy that conducts structuring and development of quality of settlement infrastructure in a sustainable manner, optimizing the potential of resources in supporting the improvement of local community welfare, guidance and technical assistance to community empowerment in handling slums, as well as the provision and development of bar economic businesses u (oriented local wisdom).